2007
DOI: 10.1001/archinte.167.22.2405
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Presentation of Women With Acute Coronary Syndromes

Abstract: Background: Optimal diagnosis and timely treatment of patients with an acute coronary syndrome (ACS) depends on distinguishing differences between popular "myths" about ischemic symptoms in women and men. Chest pain or discomfort is regarded as the hallmark symptom of ACS, and its absence is regarded as "atypical" presentation. This review describes the presenting symptoms of ACS in women compared with men and ascertains whether women should have a symptom message that is separate or different from that for me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
217
4
12

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 310 publications
(251 citation statements)
references
References 77 publications
12
217
4
12
Order By: Relevance
“…Those who have reported that there is a sex-based difference (anatomical or physiological in nature) have postulated that women do not recognize their cardiac symptoms because health educators' characterizations are based on men's experiences when women's symptoms are different from the "hallmark" symptoms -they are "atypical" and consequently not recognized as serious (O'Keefe-McCarthy, 2008). Canto et al (2007) however hypothesized that this apparent difference is more likely the result of differences in age at the time of a cardiac event, rather than being a sex difference (women are generally older than men when they first experience an acute coronary syndrome and age influences the symptom experience). Others have suggested that there are gender differences in helpseeking behavior and they are social in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Those who have reported that there is a sex-based difference (anatomical or physiological in nature) have postulated that women do not recognize their cardiac symptoms because health educators' characterizations are based on men's experiences when women's symptoms are different from the "hallmark" symptoms -they are "atypical" and consequently not recognized as serious (O'Keefe-McCarthy, 2008). Canto et al (2007) however hypothesized that this apparent difference is more likely the result of differences in age at the time of a cardiac event, rather than being a sex difference (women are generally older than men when they first experience an acute coronary syndrome and age influences the symptom experience). Others have suggested that there are gender differences in helpseeking behavior and they are social in nature.…”
Section: Introductionmentioning
confidence: 99%
“…clinically relevant scientific contributions by identifying sex-specific differences in symptoms, pathologies, and treatment response [2][3][4]. In continuation of this effort, the NIH announced new measures to enhance gender equity [5].…”
mentioning
confidence: 99%
“…[6][7] Moreover, her serial troponin T levels were slightly elevated and ECG changes were noted while she was pain free. ECG changes included inverted T waves in V2 and V3.…”
Section: Discussionmentioning
confidence: 99%